Implementation of Patient-Reported Outcomes Measurement Information System Data Collection in a Private Orthopedic Surgery Practice. (May 2018) - Haskell, Andrew; Kim, Todd
Background: The authors describe a method of collecting patient-reported outcomes (PROs) using computerized adaptive tests (CATs) in a high-volume orthopedic surgery practice with limited resources and no research coordinator. Methods: Patient-Reported Outcomes Measurement Information System CATs were collected prospectively for all clinic patients using a tablet and recorded in the electronic medical record. Scores were compared with validated national norms using single-variable t tests. Linear regression was used to assess age effects. Preoperative and postoperative pain scales were compared using paired t tests. Results: In total, 4, 524 CATs were administered during 10, 719 visits (42%), reaching 70% as more tablets were introduced. Completing the CATs required 157 seconds. Older patients took more time than younger ones ( P < .05). Compared with normalized t scores of 50 ± 10 for the US population, pain intensity was 48.0 (95% confidence interval [CI], 47.8-48.2), pain interference 58.9 (95% CI, 58.6-59.1), physical function 40.1 (95% CI, 39.9-40.3), global physical health 43.4 (95% CI, 41.9-44.9), and global mental health 41.1 (95% CI, 40.89-41.4) ( P < .05 for all). Age had a small effect on all domains ( P < .05). Approximately 20 patients would be required to demonstrate a 15% change for a 2-tailed, paired study with α = 0.05 and 80% power. After surgery, pain intensity improved from 51.9 ± 8.2 to 44.1 ± 8.5, pain interference improved from 62.5 ± 6.9 to 55.7 ± 8.4, and physical function improved from 37.3 ± 8.9 to 41.5 ± 7.9 ( P < .05 for all). Conclusions: Using tablets to administer CATs and entering the data in the electronic medical record for later retrieval was an effective technique to collect PROs. An adequate number of tablets are needed for acceptable completion rates. Modest sample size requirements for comparative studies highlight the potential of these tools and techniques. Level of Evidence: Level II, Prospective Comparative Study